Iraqi Postgraduates’ Perception And Production Of Requests In English: A Pragmatic Study - Sattar, Hiba Qusay Abdul (2011)
The speech act of requesting by Iraqi postgraduates is selected as the unit of analysis because requests often call for strategies of indirection; requests are face-threatening, and the possibility of offending someone is inherent in the act itself (Brown & Levinson, 1987). Some studies have been conducted on native speakers of Arabic concerned with speech act in general and requests in particular. However, within the Iraqi context, there is no single empirical study that has looked at the specific speech act of requesting by Iraqis in English. Hence, this study fills an existing gap in pragmatic research by looking at Iraqis’ pragmatic ability when perceiving and producing the speech act of requesting.